Genotypic characterization of extended-spectrum beta-lactamase-producing E. coli from dogs in northern Germany - Marco Werhahn Beining; Sebastian Guenther; Antina Lüebke-Becker; Stefan E. Heiden; Katharina Schaufler; Lothar Kreienbrock; Michael Schwabe (Microbiology Spectrum, 2025)
ABSTRACT Antimicrobial resistance (AMR) is a growing concern in veterinary and public health, with extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli playing a significant role. This study examined 1,000 healthy and sick dogs from a veterinary clinic in northern Germany and identified 85 ESBL-producing E. coli. Whole-genome sequencing of these isolates revealed seven phylogroups. A (38.8%) and B1 (32.9%) were the most common. Multilocus sequence typing identified 42 sequence types (STs), with the globally occurring lineages ST744 and ST10 being predominant. Single nucleotide polymorphism analysis showed the clonal circulation of ST744 among dogs in shared environments, such as households or breeders, whereas ST10 isolates displayed greater genetic diversity. ST131, a pathogenic international high-risk clonal lineage often associated with humans, was assigned to one isolate. Virulence-associated genes (VAGs) were abundant across the isolates, with siderophore systems, biofilm formation, and adherence traits being prominent. All isolates carried enterobactin genes with additional siderophore systems, such as yersiniabactin and aerobactin, present in 36 isolates. The highest number of VAGs (25) was observed in isolates belonging to the pathogenic lineages ST648 and ST405. Sixty-nine percent of the isolates were multidrug-resistant, carrying resistance genes for three or more antibiotic classes, with beta-lactam, aminoglycoside, and tetracycline resistance being the most frequent. This study highlights globally occurring E. coli lineages in companion animals and the role of close contact environments in their dissemination. Although dog-to-human transmission was not investigated in this study, these findings support the need for a One Health approach to address AMR, emphasizing the interconnected health of humans, animals, and the environment.IMPORTANCEThis study demonstrated the presence of globally significant Escherichia coli lineages in dogs and highlighted the impact of close-contact environments, such as households and breeders, on their spread. Many of the isolates exhibited genetic multidrug resistance and virulence features, posing challenges for effective treatment and control. These findings emphasize the interconnected nature of human, animal, and environmental health, underlining the need for a One Health approach to address antimicrobial resistance.